2011
DOI: 10.1007/s00464-011-2064-8
|View full text |Cite
|
Sign up to set email alerts
|

What is the best reconstruction method after distal gastrectomy for gastric cancer?

Abstract: R-Y anastomosis is superior to B-I and B-II with Braun anastomosis in terms of frequency of bile reflux, despite the fact that there is no difference in the postoperative quality-of-life index and nutritional status between reconstructive procedures. The laparoscopic approach is the better option than open surgery in terms of QOL in the immediate postoperative period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
108
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(117 citation statements)
references
References 23 publications
8
108
1
Order By: Relevance
“…This observation held true on separate subset analyses for distal and subtotal gastrectomy patients. Similarly, in a prospective randomized study of 159 gastrectomy patients who underwent B1, B2, or RY reconstruction, Lee et al [4] found a comparable impact of the three reconstruction methods on nutritional parameters (albumin level, protein level, total lymphocyte count, transferrin level, body weight, and body mass index) measured at 3, 6, 12, and 24 months postoperatively. In another randomized trial, Csendes et al [5] found that there were no differences in the rates of postgastrectomy diarrhea (9.1 % vs. 9.7 %), dumping syndrome (6 % vs. 3.2 %), and weight gain (78.8 % vs. 90.3 %) between patients who underwent either B2 reconstruction or RY reconstruction.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…This observation held true on separate subset analyses for distal and subtotal gastrectomy patients. Similarly, in a prospective randomized study of 159 gastrectomy patients who underwent B1, B2, or RY reconstruction, Lee et al [4] found a comparable impact of the three reconstruction methods on nutritional parameters (albumin level, protein level, total lymphocyte count, transferrin level, body weight, and body mass index) measured at 3, 6, 12, and 24 months postoperatively. In another randomized trial, Csendes et al [5] found that there were no differences in the rates of postgastrectomy diarrhea (9.1 % vs. 9.7 %), dumping syndrome (6 % vs. 3.2 %), and weight gain (78.8 % vs. 90.3 %) between patients who underwent either B2 reconstruction or RY reconstruction.…”
Section: Discussionmentioning
confidence: 81%
“…In addition, both studies showed the incidence of bile reflux gastritis to be higher in the B1 group (31 % vs. 21 % and 48 % vs. 26 %) on the basis of endoscopy performed 1 year postoperatively [2,3]. Furthermore, a subsequent randomized trial of 159 patients from Korea comparing all three reconstruction types showed that although bile reflux gastritis was significantly less common 1 year after RY reconstruction (compared with B1 or B2 reconstruction), a comparison of quality-oflife and nutritional parameters 1 year postoperatively revealed no differences between the three groups [4]. Lastly, the latest results (12-21 years) of a prospective randomized study from Chile comparing B2 and RY reconstruction after gastrectomy for benign disease showed a higher incidence of gastroesophageal reflux symptoms after B2 reconstruction versus RY reconstruction (33 % vs. 3 %), endoscopic appearance of short-segment Barrett's esophagus (25 % vs. 3 %), and histologically proven intestinal metaplasia (21 % vs. 3 %) [5].…”
Section: Introductionmentioning
confidence: 98%
“…After distal gastrectomy, Roux-en-Y reconstruction seems superior to Billroth I and Billroth II reconstructions in terms of functional outcomes and long-term endoscopic results; however, no clear conclusions are available in the literature, and the choice of the procedure could be based on the surgeon's experience [15,16]. After total gastrectomy, Roux-en-Y reconstruction remains the easiest solution, with satisfactory functional results.…”
Section: Surgical Therapy Resectionmentioning
confidence: 99%
“…Compared to other surgeries in gastrointestinal tract, there are more complicated guidelines for lymph node dissection around major nominated vessels and various ways of laparoscopic reconstruction in laparoscopic gastric cancer surgery which are continuously investigated and modified (26)(27)(28). To evaluate feasibility of SIDG for gastric cancer, we should consider these troublesome characteristics and its adequate solution in advance.…”
Section: Single Incision Distal Gastrectomy (Sidg)mentioning
confidence: 99%